Analisis Keselamatan dan Kesehatan Kerja Bidang Freight Forwader Menggunakan Metode HIRADC - Tatan Sukwika; Harvin Dwipa Pranata (Universitas Negeri Gorontalo, 2022)
Companies engaged in the freight forwarders or transportation services with activities that pose a risk to the safety and health of workers certainly have the potential to cause danger, starting from the loading-unloading process, the delivery to storage. Therefore, a study on occupational safety and health (K3) is needed. The purpose of this research is to identify occupational risks on freight forwarders and to calculate the level of risk according to the level of likelihood and severity severity. The method uses HIRADC, data collected through observation and questionnaires. Respondents in this study used saturated sampling that is all employees who are at PT. Wardani Srikandi Karya numbered 25 people. The results of the analysis show that there are 81 levels of hazard risk with details of 42% low risk, 54% moderate risk, and 4% high risk level, while the extreme risk level is zero. The conclusion of the research is that freight forwarder companies are dominated by the medium category. The managerial implication that can be recommended is the need for periodic control through elimination, substitution, engineering, administrative and PPE techniques.